Monetary Policy Committees, Learning and Communication - Weber, Anke. (Washington, D.C. : International Monetary Fund, 2010)
This paper considers optimal communication by monetary policy committees in a model of imperfect knowledge and learning. The main policy implications are that there may be costs to central bank communication if the public is perpetually learning about the committee's decision-making process and policy preferences. When committee members have heterogeneous policy preferences, welfare is greater under majority voting than under consensus decision-making. Furthermore, central bank communication under majority voting is more likely to be beneficial in this case. It is also shown that a chairman with stable policy preferences who carries significant weight in the monetary policy decision-making process is welfare enhancing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet